Portraying Information Systems as a Member of Various Asterisms in the Galaxy of Science - Kroeze, Jan H. (Phronimon, 2022)
The discipline of Information Systems is often viewed as a social science. Information Systems research and teaching pertain to the management and sociological issues of the computing field. It also includes programming and systems analysis, design and development. It is, therefore, challenging to plot Information Systems on a continuum of disciplinary clusters. Depending on the viewpoint held on the scientific world, the groups of disciplines take on different forms. Although metaphors are often used in Information Systems to portray complex ideas in understandable ways, only a few papers could be found that explain the interdisciplinary nature of the discipline metaphorically. To fill this gap, this article uses the astronomical concepts of galaxy, constellation and asterism to explain the place of Information Systems within the scientific domain. An asterism is a grouping of stars which may be part of various constellations. Six different Information Systems asterisms are proposed. The conceptual reflection in the article offers a fresh perspective on the interdisciplinary nature of Information Systems to the philosophy of science. The article illustrates the proposed metaphors with some existing examples to validate the concept. Suggestions for future research are also provided.